Evaluation of the Wound Healing Potential of Some Natural Polymers on Three Experimental Models - Calin Vasile Andritoiu; Corina Elena Andriescu; Maricel Danu; Cristina Lungu; Bianca Ivanescu; Cornel Havarneanu; Marcel Popa (Pharmaceuticals, 2021)
The aim of this paper was the preparation and investigation of the wound healing properties of four topical formulations based on natural polymers such as collagen, chitosan, lyophilized egg white, and a mixture of them. The therapeutic assessment of these four ointments was carried out in vivo on the incision, excision, and thermal burn wounds induced on Wistar rats. The treatment was applied topically on wounds once a day, for 21 days. The experimental results were analyzed from a clinical and histopathological point of view. The rheological characterization of the topical formulations was also performed in order to verify their spreadability and structural stability. All ointments had a positive effect on wound contraction and re-epithelization processes, but the one based on total polymers had a significant healing potential on the designed cutaneous lesions due to its synergistic effects.